(untitled) (The International Journal for Scientific Research, 2025)
Purpose: Sports has traditionally used as a social activity but today it is taking a new vital role of nation brand building and diplomacy. however, only a few studies have pursued this topic in the recent past. As sports fans become more identified with their respective favorite sporting activities, governments have identified an opportunity to influence the behavior to promote their national agenda. The current study aims at unravelling how mega motorsport events in Saudi Arabia have been leveraged for nation branding and economic diversification efforts. Methodology: The study adopted a mixed-methods design, involving Saudi motorsport stakeholders, including fans. The survey was distributed through online channels, such as university networks and social media platforms relevant to motorsport communities in Saudi Arabia. In addition, structured interviews were conducted. The collected data was analyzed to assess the effectiveness of motorsport events in promoting the Kingdom’s brand image, in line with Vision 2030. Findings: The results indicated that motorsport events positively influenced the country’s image in the global stage with most respondents indicating that the mega events portrayed the nation as innovative and progressive. These positive sentiments were associated with growing sports tourism and growing sports sponsorships. It also indicates that the sport has promoted the attainment of various targets in the vision 2030 repulsing the sportswashing claims levelled by critics and human right agencies. Value of the study: This study expands the understanding of the economic and reputational ROI of mega sporting events. It would also contribute useful insights on marketers on strategies employable to influence fandom attitude and perception towards an nation or a given brand. management can analyze the importance of sports and fandom and how to leverage this identity can be channeled for the benefit of the brand.